Next Steps for the Relative Education Hypothesis. Issue 5 (October 2021) - Horowitz, Jonathan
The relative education hypothesis states that in contexts where university degrees are scarce, workers with bachelor's degrees are sought after and enter cognitively skilled occupations; but as education expands across birth cohorts, some workers with bachelor's degrees are unable to maintain their position in the labor market. In an earlier ASR article (Horowitz 2018), I found support for this argument; however, Furey (2021) shows model instability in estimates of the education–skill relationship. We should treat the results from these two studies as a range of possible estimates, and carefully consider interpretation of the findings in the context of the selected reference categories. Future revisions of the relative education hypothesis should consider that absolute and relative education effects might not shift concurrently, and also that labor market experiences may vary considerably by field of study and occupation.